2017
DOI: 10.1038/s41598-017-09751-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-factors including Inflammatory/Immune, Hormones, Tumor-related Proteins and Nutrition associated with Chronic Prostatitis NIH IIIa+b and IV based on FAMHES project

Abstract: Chronic prostatitis (CP) is a complex disease. Fragmentary evidence suggests that factors such as infection and autoimmunity might be associated with CP. To further elucidate potential risk factors, the current study utilized the Fangchenggang Area Male Health and Examination Survey (FAMHES) project; where 22 inflammatory/immune markers, hormone markers, tumor-related proteins, and nutrition-related variables were investigated. We also performed baseline, regression, discriminant, and receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
(65 reference statements)
0
5
0
2
Order By: Relevance
“…Etiology of CP is not fully understood and treatment is frequently unsuccessful [1][2][3] . Fragmentary epidemiological evidence indicates that risk factors such as infection, autoimmunity, inflammation, excessive amounts of tumor-related proteins, imbalance of hormones and nutritionrelated variables, including Zn and some other trace elements (TEs) as micronutrients, may be associated with CP [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiology of CP is not fully understood and treatment is frequently unsuccessful [1][2][3] . Fragmentary epidemiological evidence indicates that risk factors such as infection, autoimmunity, inflammation, excessive amounts of tumor-related proteins, imbalance of hormones and nutritionrelated variables, including Zn and some other trace elements (TEs) as micronutrients, may be associated with CP [4] .…”
Section: Introductionmentioning
confidence: 99%
“…4 present data of Zn concentration in EPF of normal prostates obtained by the destructive and non-destructive analytical methods, respectively.…”
mentioning
confidence: 99%
“…Studies have confirmed that inflammation and immune factors (IgE, complement C4, complement C3, CRP, ASO, and RF) and hormone elements (Osteoc, FSH, testosterone, and insulin) are significantly related to the occurrence of prostatitis [ 33 ]. It showed that this study was highly consistent with the previous research results of Chen et al [ 33 ]. There were five SNP sites with a positive causal association between complement C4 and chronic prostatitis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Воспалительный процесс в предстательной железе (ПЖ) не всегда проявляется клинической симптоматикой, а часто сопровождается только увеличением количества лейкоцитов в секрете ПЖ или эякуляте, что обнаруживается случайным образом при профилактических осмотрах или при обследовании по поводу бесплодия или нарушения копулятивной функции [1][2][3][4][5]. Достаточно часто такая бактериоспермия остается нераспознанной, ухудшая параметры спермы и снижая вероятность наступления беременности, даже при проведении экстракорпорального оплодотворения [6][7][8][9][10][11].…”
Section: Introductionunclassified